Septic arthritis of the hip in a Cambodian child caused by multidrug-resistant Salmonella enterica serovar Typhi with intermediate susceptibility to ciprofloxacin treated with ceftriaxone and azithromycin. (August 2014) - Pocock, J. M.; Khun, P. A.; Moore, C. E.; Vuthy, S.; Stoesser, N.; Parry, C. M.
<x content-type="archive" xml:space="preserve">Abstract</x> Septic arthritis is a rare complication of typhoid fever. A 12-year-old boy without pre-existing disease attended a paediatric hospital in Cambodia with fever and left hip pain. A hip synovial fluid aspirate grew multidrug-resistant Salmonella enterica ser. Typhi with intermediate susceptibility to ciprofloxacin. Arthrotomy, 2 weeks of intravenous ceftriaxone and 4 weeks of oral azithromycin led to resolution of symptoms. The optimum management of septic arthritis in drug-resistant typhoid is undefined.